2019
DOI: 10.1158/1535-7163.mct-18-0854
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of A Novel EGFR-Targeting Antibody–Drug Conjugate, SHR-A1307, for the Treatment of Solid Tumors Resistant or Refractory to Anti-EGFR Therapies

Abstract: Although inhibiting EGFR-mediated signaling proved to be effective in treating certain types of cancers, a quickly evolved mechanism that either restores the EGFR signaling or activates an alternative pathway for driving the proliferation and survival of malignant cells limits the efficacy and utility of the approach via suppressing the EGFR functionality. Given the fact that overexpression of EGFR is commonly seen in many cancers, an EGFR-targeting antibody-drug conjugate (ADC) can selectively kill cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…He et al (2019) reported modifications of dolaproine along with aromatic ring halogenated analogues of MMAF ( 89 – 93 ). Cyclopropyl MMAF ( 89 ) and cyclopropyl- o -chloro-MMAF ( 90 ) showed excellent activity, with GI 50 values of 1.1 and 1.06 nM, respectively, against the SB-BR-3 HER2+ cell line.…”
Section: Sar Of Auristatins and Their Antibody Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al (2019) reported modifications of dolaproine along with aromatic ring halogenated analogues of MMAF ( 89 – 93 ). Cyclopropyl MMAF ( 89 ) and cyclopropyl- o -chloro-MMAF ( 90 ) showed excellent activity, with GI 50 values of 1.1 and 1.06 nM, respectively, against the SB-BR-3 HER2+ cell line.…”
Section: Sar Of Auristatins and Their Antibody Conjugatesmentioning
confidence: 99%
“…Based on the highest cytotoxic activity ratio of >1500 of ADC and free toxin payload, the noncleavable anti-EGFR (hR3)-ADC SHR-A1307 (GI 50 0.031 nM) ( 94a ) containing cyclopropyl-fluoro-MMAF 93 (GI 50 47.7 nM) was selected for further characterization and development, with the expectation that the lysosomal released payload would not be subject to cellular efflux and thus exert less toxicity. SHR-A1307 showed broad-spectrum efficacy against a series of HER2+ tumor xenograft murine models at 1.2 and 4 mg/kg including drug-resistant models, without exhibiting overt toxicities at 40 mg/kg at repeated doses, indicating a 10–20-fold therapeutic window (2019) . However, it was not as well tolerated in cynomolgus monkeys at 10 mg/kg after repeated dosing.…”
Section: Sar Of Auristatins and Their Antibody Conjugatesmentioning
confidence: 99%
“…He et al developed a new ADC targeting EGFR, namely SHR-A1307 ( 47 ) (Fig. 13 ), for the treatment of solid tumors resistant or refractory to EGFR-targeted therapy [ 142 ]. SHR-A1307 ( 47 ) has intermediate ability to block EGFR affinity for hR3 and selectively binds to cancer cells expressing EGFR while avoiding inhibitory effects on normal cells.…”
Section: Egfr-dependent Drug Resistance Mechanismsmentioning
confidence: 99%
“…Another MMAF analog considered for ADC development was a cyclopropyl fluoro derivative, which was incorporated into the ADCs 48 and 49 in an attempt to address some pharmacological issues such as toxicity, expecting that the payload would not be subject to cellular efflux and thus exert less toxicity. Thus, the ADCs, consisting of the anti-EGFR and of the anti-c-MET antibodies conjugates, were prepared, revealing a DAR of 2 [ 104 ]. While the first was not well tolerated in preclinical studies at 10 mg/kg doses, the second displayed a better pharmacological profile, combined with strong cytotoxic activity against c-MET-expressing cell lines, including NCI-H1993, MKN-45, and HCCLM3 with IC 50 values of 16.3, 7.8 and 3.2 ng/mL, respectively [ 105 ].…”
Section: Chemistry and Biology Of Marine Antibody-drug Conjugatesmentioning
confidence: 99%